Michelangelo's sculpture : selected essays - Steinberg, Leo, 1920-2011 (Steinberg, Leo, 1920-2011. Essays. 2018., 2018)
Leo Steinberg was one of the most original and daring art historians of the twentieth century, known for taking interpretative risks that challenged the profession by overturning reigning orthodoxies. In essays and lectures that ranged from old masters to contemporary art, he combined scholarly erudition with an eloquent prose that illuminated his subject and a credo that privileged the visual evidence of the image over the literature written about it. His works, sometimes provocative and controversial, remain vital and influential reading. For half a century, Steinberg delved into Michelangelo's work, revealing the symbolic structures underlying the artist's highly charged idiom. This volume of essays and unpublished lectures explicates many of Michelangelo's most celebrated sculptures, applying principles gleaned from long, hard looking.